A Sociolinguistic Analysis of Language Styles in the Main Characters’ Utterances in Bride Wars (2009) Based on Martin Joos’ Five-Style Framework - Mieyrandha, Mieyrandha; Retsi, Olga Dona; Haryani, Tutik; Maharani, Laura Meylinda (Journal of English Language and Education, 2026)
This study analyzes the differences in linguistic style in Bride Wars (2009) using Martin Joos' (1967) Five Styles of Speech as a guide. The study employs a descriptive qualitative design to examine 45 curated statements from the film through the documentation method. There were five types of information: frozen, formal, consultative, casual, and intimate. This was done according to Joos' rules for language. Some of these are the level of formality in the conversation, the words used, the way feedback is given, and how close the people are to each other. The results show that the most common style is casual (40%), then consultative (22.22%), intimate (20%), formal (13.33%), and frozen (4.44%). The results show that changes in the film's style are mostly due to changes in emotions and relationships, not changes in the institution's hierarchy. You can be sarcastic and fight in a casual way, but you can also show that you're friends and close. Being formal doesn't mean you're in charge; it means you're not close to someone. People still talk to each other at work the same way. In scenes of reconciliation, the intimate style is very clear, which shows that things are back to normal between the two people. People don't use frozen style very often, and when they do, it's only in formal settings. The research shows that language style is a dynamic continuum and a useful sociolinguistic tool for figuring out where you fit in film discourse.